Adaptive Programming in Fragile, Conflict and Violence-Affected Settin gs, What Works and Under What Conditions?: The Case of Institutions fo r Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Itad, Oxfam, 2019)
Adaptive Management involves a dynamic interaction between three eleme nts: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Develo pment (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability i n fragile, conflict and violence-affected settings (FCVAS). The resear ch examines some of the assertions around the adaptive management appr oach and explores if and how adaptive approaches, including rapid lear ning and planning responses (fast feedback loops and agile programming ) are particularly relevant and useful for citizen empowerment and gov ernment accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery